Study of Kernel Oils Properties of Selected Plants from Kahuzi-Biega National Park and Surroundings, South-Kivu, Democratic Republic of Congo - Minzangi, Melchias Kazadi; Kanimba, Junior Kabongo; Kongbo, Théophyle Tambala; Kaaya, Archileo Natigo; Kansiime, Frank; Mukaya, Augustin Malumba (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
The floristic composition conditions most habitats in the world and this, ultimately, conditions the presence or absence of several animal species and of all biodiversity. Protected areas are the cornerstone of efforts to conserve the planet’s species and ecosystems. The rising consumption of edible vegetable oils underscores the importance of understanding their medicinal and nutritional value. Kahuzi-Biega National Park in the Democratic Republic of the Congo is home to various plants as sources of edible oil for food preparations and medicinal therapy. This study aimed to assess the oil yield and to characterise oils obtained from eleven plants growing in this park and its surroundings. These were Carapa grandiflora, Carapa procera, Cardiospermum halicacabum, Maesopsis eminii, Millettia dura, Myrianthus arboreus, Myrianthus holstii, Pentaclethra macrophylla, Podocarpus usambarensis, Tephrosia vogelii and Treculia africana. Oils were extracted using ethyl ether in a Soxhlet extractor, and physicochemical characteristics were determined using standard methods of the American Oil Chemists Society. The seed oil content obtained ranged from 17.2% (T. vogelii) to 64.4% (P. usambarensis). The oil specific gravity varied from 0.8050 to 0.9854; the oils' melting point ranged from -12 to 32°C; the oil saponification values from 182.5 to 260.9 mg KOH/g; the oil acidity index from 1.74 to 5.31 mg KOH/g, and the unsaponifiable matter from 0.54 to 2.25%. The plant seed oils content reported in this study is comparatively higher than some food crop plants such as soybean and olive. Five of these oils have an oil melting range as that of edible oils. C. grandiflora, C. halicacabum, M. eminii and the two species of Myrianthus are in the range of common cooking oils by their specific gravity values. P. usambarensis seed oil, with its relatively high unsaponifiable matter content, can have efficacy as a cosmetic.